A nationwide study on parathyroid carcinoma. (3rd July 2017) - Ryhänen, Eeva M.; Leijon, Helena; Metso, Saara; Eloranta, Eija; Korsoff, Pirkko; Ahtiainen, Petteri; Kekäläinen, Päivi; Tamminen, Marjo; Ristamäki, Raija; Knutar, Otto; Löyttyniemi, Eliisa; Niskanen, Leo; et al.
Abstract: Background: Parathyroid carcinoma (PC) is rare and diagnostically challenging. Reported outcomes are rather poor and the incidence might be increasing. Material and methods: We performed a nationwide study on all cases ( n = 32) diagnosed in 2000–2011 in Finland, and compared clinical and histopathological characteristics and outcome to atypical parathyroid (APA; n = 28) and parathyroid adenomas (PA; n = 72). The incidence in years 1955–1999 was compared to that in 2000–2013. Results: Preoperatively, calcium and parathyroid hormone concentrations were higher in PC compared to APA and PA (1.76, 1.56 and 1.44 mmol/l, p < .001; and 989, 355 and 160 μmol/l, p < .001, respectively). Calcium was ≤1.77 mmol/l for all PAs. Hospitalization (44% vs. 22% and 3%, respectively, p = .01), renal (50% vs. 48% vs. 22%, respectively, p = .01) and bone (47% vs. 15% vs. 38%, respectively p = .002) manifestations were more common. PC and APA tumors were larger than PA ( p < .001). Histopathological characteristics of PC compared to PA are increased mitotic activity ( p = .001), chief cells ( p = .003), diffuse growth pattern ( p < .001), higher Ki67 ( p < .001) and negative parafibromin ( p < .001). One PC (1/18) and one APA (1/16) patient had a CDC73 mutation. After 6.7 (2–13.9) years of follow-up, 9.4% of PC had residual, 21% recurrent disease and 12.5% died of disease. Overall mortality did not differ between subgroups ( p = .094). Recurrent PC was characterized by vascular invasion, lymph node metastases, high mitotic activity, necrosis and negative parafibromin. Incidence increased from 1.42 (range 0.52–2.14) to 7.14 (range 3.42–10.38)/10.000.000/years; ( p < .001). Conclusions: PC associates with severe primary hyperparathyroidism and must be suspected if calcium ≥1.77 mmol/l. The prevalence of CDC73 germline mutations in PC and APA in Finland is 6%. PC has distinct histopathological characteristics and its incidence has increased over the past decades.